Financial Incentives to Work - Conceptions and Results in Great Britain, Ireland and Canada - Wolfgang Ochel (Center for Economic Studies and ifo Institute (CESifo), 2001)
Some English speaking countries provide employment-conditional tax credits and benefits with a view to increasing employment and improving family income in the low wage brackets. This article deals with Great Britain's Working Families' Tax Credit, Ireland's Back to Work Allowance and her Family Income Supplement, as well as Canada's Child Tax Benefit and her Self-sufficiency Project. It analyses the effects of these programmes and examines whether they can be transplanted to continental European countries.
Keywords: 330